The Complex Diversity of Southeast Asian Postsecondary Education - Altbach, Philip G. (International Higher Education, 2017)
Higher education in Southeast Asia constitutes a complex mosaic of cultures, languages, and academic traditions. This article argues that while there are some similarities, the many variations make it difficult to generalize about the region or to create a common approach to higher education development.